2014
DOI: 10.3748/wjg.v20.i45.17011
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in colorectal cancer: Role in metastasis and clinical perspectives

Abstract: Colorectal cancer (CRC) is the third most common malignancy and the third leading cause of cancer related deaths in the United States. Almost 90% of the patients diagnosed with CRC die due to metastases. MicroRNAs (miRNAs) are evolutionarily conserved molecules that modulate the expression of their target genes post-transcriptionally, and they may participate in various physiological and pathological processes including CRC metastasis by influencing various factors in the human body. Recently, the role miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 92 publications
1
52
0
Order By: Relevance
“…In the past, miRNAs have been found to be frequently deregulated in CRC, and some miRNAs were found to be associated with particular clinicopathological features of CRC, such as metastasis, recurrence and prognosis [17][18][19]. Moreover, compelling evidence indicates that miRNAs may play important roles in CRC progression and may directly contribute to the proliferation, avoidance of apoptosis and metastasis of CRC [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, miRNAs have been found to be frequently deregulated in CRC, and some miRNAs were found to be associated with particular clinicopathological features of CRC, such as metastasis, recurrence and prognosis [17][18][19]. Moreover, compelling evidence indicates that miRNAs may play important roles in CRC progression and may directly contribute to the proliferation, avoidance of apoptosis and metastasis of CRC [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that the deregulation and dysfunction of miRNAs is key in the development and progression of CRC (22,23). Increased expression of oncomiRs and decreased expression of tsmiRs have been observed in CRC tissues as compared with adjacent non-tumor tissues (24).…”
Section: Discussionmentioning
confidence: 99%
“…12 In CRC, several studies have reported that miRNAs are involved in tumor progression and metastasis and are therefore suggested as potential prognostic biomarkers. 13,14 It has been demonstrated that the transcription factor TWIST-1 induces miR-10b which in turn inhibits the translation of a member of the homeobox (HOX) gene family, HOXD10. The expression of HOXD10 is lost during the malignant progression of breast cancer, resulting in the increased levels of the pro-metastatic gene RHOC.…”
Section: Introductionmentioning
confidence: 99%